2017
DOI: 10.1021/acsami.7b10136
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ti and Cr Adhesion Layers on Ultrathin Au Films

Abstract: Efficient adhesion of gold thin films on dielectric or semiconductor substrates is essential in applications and research within plasmonics, metamaterials, 2D materials, and nanoelectronics. As a consequence of the relentless downscaling in nanoscience and technology, the thicknesses of adhesion layer and overlayer have reached tens of nanometers, and it is unclear if our current understanding is sufficient. In this report, we investigated how Cr and Ti adhesion layers influence the nanostructure of 2-20 nm th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
131
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(147 citation statements)
references
References 41 publications
3
131
1
Order By: Relevance
“…To reduce the percolation threshold of ultrathin gold films, adhesion or seed layers of Ti, Cr, Ni, Pt, or Ge are commonly used. However, these adhesion layers significantly affect the optical and electrical properties of ultrathin metal nanostructures . Recently, the organosilane‐based adhesion layers (mercaptosilanes and aminosilanes) were used for the deposition of sub‐10 nm thick continuous Au films on silicon and glass surfaces .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the percolation threshold of ultrathin gold films, adhesion or seed layers of Ti, Cr, Ni, Pt, or Ge are commonly used. However, these adhesion layers significantly affect the optical and electrical properties of ultrathin metal nanostructures . Recently, the organosilane‐based adhesion layers (mercaptosilanes and aminosilanes) were used for the deposition of sub‐10 nm thick continuous Au films on silicon and glass surfaces .…”
mentioning
confidence: 99%
“…Recently, the organosilane‐based adhesion layers (mercaptosilanes and aminosilanes) were used for the deposition of sub‐10 nm thick continuous Au films on silicon and glass surfaces . However, organosilanes are not compatible with nonoxidized silicon surfaces and poorly compatible with standard lift‐off procedures, that imposes severe limitations to their use as adhesion layers . Adhesion layers based on organosilanes are also inefficient for the deposition of atomically thin metal films and does not move us closer to the deposition of 2D layers from bulk plasmonic metals.…”
mentioning
confidence: 99%
“…DC sputtering in argon ambient was used to deposit a 20 nm thick titanium adhesion layer . Subsequently, a 120 nm thick layer of platinum was deposited without breaking the vacuum.…”
Section: Methodsmentioning
confidence: 99%
“…More importantly, removing 10 nm thick titanium adhesion layer from nanohole array by etching drastically decreases the optical resonance bandwidths. Another study has found that Cr can interdiffuse more with Au to form Cr-Au alloy than Ti, suggesting Ti is the optimal adhesion layer for Au-based PANTFs [33]. The adhesion layer has been engineered to minimize the plasmonic damping by depositing less than 1 nm adhesive, which prevents the layer to overlap with the hotspots of PANTFs [34]; however, thinner layer of adhesive also means low stability of PANTFs.…”
Section: Intermediate Layer For Stabilizing Pantfsmentioning
confidence: 99%